Problems Of Providing Medical and Social Support to Patients with Tuberculosis and Ways to Solve Them - Sultanov Golibjon Inamidinovich (Genius Journals, 2024)
The issue of providing medical and social care to patients with tuberculosis in modern conditions is an extremely important component of the system of anti-tuberculosis measures. The presented work identifies key problem areas in the provision of medical and social measures to patients with tuberculosis, taking into account the changes that have occurred in the state at the present stage. New concepts and definitions of medical and social assistance and medical and social support are proposed. An option has been proposed for organizing medical and social support in the anti-tuberculosis service with optimal expenditure of budgetary funds and the absence of legal contradictions: the creation of a group of medical and social support on the basis of anti-tuberculosis institutions. A variant of the structure, staff, and functioning algorithm is given
Keywords: medical and social assistance; healthcare organization; tuberculosis